A Comparative Analysis of Shariah Governance Framework of Islamic Bank in Malaysia and Pakistan - Ahmad, Zaki; Muneeza, Aishath; Rahman, Md. Mahfujur; Mahomed, Ziyaad (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2023)
The aim of this paper is to investigate the differences between the contemporary Shariah governance frameworks of Malaysia and Pakistan. The study also examines the ways in which the Shariah governance frameworks of both countries can complement each other. This research concludes that the SGF principles of both countries under discussion abide by the AAOIFI and IFSB guidelines regarding SGF. Many aspects of the SGF of Malaysia are similar to the SGF of Pakistan. For example, both structures need to further develop the ethical aspect. While the similarities are plentiful, a few differences can be found between the two as well. This research provides insights to policy makers, regulators, and practitioners on approaches in governance policy and an assessment of the governance scope adopted by Malaysia and Pakistan via their respective SGFs. The SGFs have also been assessed for their conformance to international standards, including the AAOIFI and the IFSB.